PERLINDUNGAN HUKUM TERHADAP NASABAH ATAS PENGGUNAAN LAYANAN ELEKTRONIK BANKING (E-BANKING) PADA BANK RAKYAT INDONESIA (RISET PADA BANK RAKYAT INDONESIA UNIT MELATI) - IVAN SYAH (JURNAL CIVIL LAW USU, 2013)
Abstract  : Banking is a financial institution that provides services to its users or clients. Development of science, information and technology, providing the ease of development of the banking system itself, with the development of systems and services in order to facilitate and pamper its customers. With regard to flexibility, efficiency, and practicality. Thus was born a new method in the development of services in banking for customers, where the system is called electronic banking, or ordinary with the term e-banking which allows customers service users can make use of it, wherever and whenever, it is not limited by time with the service. As in the making of this thesis uses interviews and questionnaires and the method or approach to the type of normative legal research and field research, where research is conducted in the research done by examining library materials relating to this issue and conduct field research at Bank Rakyat Indonesia Research Field Unit as the place authors, the issues raised by the authors is how the legal protection for the use of electronic banking services are used by customers, and the responsibilities given by the bank in case of losses in the bank's customers for their negligence. So through this paper is expected to be useful for the protection of the general public so that customers become more secure. In the development that occurs does not eliminate the possibility of cracks commonly used to make profits themselves by parties who are not responsible. And in the end the bank as a provider of e-banking is also trying to provide the best service, remedy efforts to protect its customers. However, in case of loss due to the bank or the efforts of others, the legal options available to customers are: 1. Through the efforts of peace or a complaint to the bank, and 2. Through mediation or the courts as a last resort to do by the customer if the effort pesuasif on the first attempt felt failed. Keyword  : Bank, Customer, Elektronic Banking